Listeria monocytogenes as a cause of spontaneous bacterial peritonitis: a rare entity - Bilal Shaikh; Ranjan Pathak; Naba Raj Mainali; Shobhit Gupta (Greater Baltimore Medical Center, 2015)
Listeria is an uncommon cause of spontaneous bacterial peritonitis (SBP) in the United States. Listeria should be suspected as a cause of SBP when the patient has diphtheria-like organisms on ascitic/blood cultures, iron overload/hemochromatosis, exposure to farm animals, or poor response to empiric therapy within 48-72 h. Diagnosis of SBP is made if the ascitic fluid shows polymorphonuclear cell count >250 cells/mm3 without an intra-abdominal source of infection. Ampicillin with or without an aminoglycoside is the treatment of choice. Trimethoprim-sulfamethoxazole is recommended for prophylaxis in patients with a previous episode of Listeria SBP.